Advances and challenges in the field of plasma polymer nanoparticles - Choukourov, Andrei; Pleskunov, Pavel; Nikitin, Daniil; Titov, Valerii; Shelemin, Artem; Vaidulych, Mykhailo; Kuzminova, Anna; Solař, Pavel; Hanuš, Jan; Kousal, Jaroslav; Kylián, Ondřej; Slavínská, Danka; et al. (Beilstein Journal of Nanotechnology, 2017)
This contribution reviews plasma polymer nanoparticles produced by gas aggregation cluster sources either via plasma polymerization of volatile monomers or via radio frequency (RF) magnetron sputtering of conventional polymers. The formation of hydrocarbon, fluorocarbon, silicon- and nitrogen-containing plasma polymer nanoparticles as well as core@shell nanoparticles based on plasma polymers is discussed with a focus on the development of novel nanostructured surfaces.
Keywords: gas aggregation cluster source; nanocomposite; nanoparticles; plasma polymer; sputtering

(untitled) - Jenkins, A. D.; Kratochvíl, P.; Stepto, R. F. T.; Suter, U. W. (Pure Appl. Chem., 1996)

Plasma Polymerization - Yasuda, V. H. (Academic Press, 1985)

Plasma Polymerization Processes (Plasma Technology) - Biedermann, H.; Osada, Y. (Elsevier, 1992)

Plasma polymer films - Biedermann, H. (Imperial College Press, 2004)

(untitled) - Friedrich, J. (Plasma Processes Polym., 2011)

(untitled) - Williams, T.; Hayes, M. W. (Nature, 1967)

(untitled) - Denaro, A. R.; Owens, P. A.; Crawshaw, A. (Eur. Polym. J., 1968)

(untitled) - Neisewender, D. D. (Adv. Chem., 1969)

(untitled) - Thompson, L. F.; Smolinsky, G. (J. Appl. Polym. Sci., 1972)

(untitled) - Kobayashi, H.; Bell, A. T.; Shen, M. (J. Appl. Polym. Sci., 1973)

(untitled) - Vladimirov, S. V.; Ostrikov, K. (Plasmas Polym., 2003)

(untitled) - Zyn, V. I.; Potapov, V. K.; Tuzov, L. S.; Shterenberg, A. M. (High Energy Chem., 1986)

(untitled) - Bouchoule, A.; Plain, A.; Boufendi, L.; Blondeau, J. P.; Laure, C. (J. Appl. Phys., 1991)

(untitled) - Bouchoule, A.; Boufendi, L. (Plasma Sources Sci. Technol., 1993)

(untitled) - Boufendi, L.; Bouchoule, A. (Plasma Sources Sci. Technol., 1994)

(untitled) - Hollenstein, C.; Schwarzenbach, W.; Howling, A. A.; Courteille, C.; Dorier, J.-L.; Sansonnens, L. (J. Vac. Sci. Technol., A, 1996)

(untitled) - Kersten, H.; Deutsch, H.; Stoffels, E.; Stoffels, W. W.; Kroesen, G. M. W.; Hippler, R. (Contrib. Plasma Phys., 2001)

(untitled) - Denysenko, I. B.; Ostrikov, K.; Xu, S.; Yu, M. Y.; Diong, C. H. (J. Appl. Phys., 2003)

(untitled) - De Bleecker, K.; Bogaerts, A.; Goedheer, W.; Gijbels, R. (IEEE Trans. Plasma Sci., 2004)

(untitled) - Melikhov, K. G.; Shterenberg, A. M.; Zyn, V. I. (J. Phys. D: Appl. Phys., 2006)

(untitled) - Cavarroc, M.; Mikikian, M.; Tessier, Y.; Boufendi, L. (Phys. Rev. Lett., 2008)

(untitled) - Larriba-Andaluz, C.; Girshick, S. L. (Plasma Chem. Plasma Process., 2017)

(untitled) - Deschenaux, C.; Affolter, A.; Magni, D.; Hollenstein, C.; Fayet, P. (J. Phys. D: Appl. Phys., 1999)

(untitled) - Stoykov, S.; Eggs, C.; Kortshagen, U. (J. Phys. D: Appl. Phys., 2001)

(untitled) - Mao, M.; Benedikt, J.; Consoli, A.; Bogaerts, A. (J. Phys. D: Appl. Phys., 2008)

(untitled) - Do, H. T.; Sushkov, V.; Hippler, R. (New J. Phys., 2009)

(untitled) - Andreeva, A. V.; Kutsarev, I.; Shatsky, A. V.; Shterenberg, A. M.; Zyn, V. I. (Plasma Processes Polym., 2012)

(untitled) - Vinogradov, G. K.; Imanbayev, G. Z.; Polak, L. S.; Slovetsky, D. I. (High Energy Chem., 1983)

(untitled) - Takahashi, K.; Tachibana, K. (J. Vac. Sci. Technol., A, 2001)

(untitled) - Takahashi, K.; Tachibana, K. (J. Appl. Phys., 2001)

(untitled) - Ostrikov, K. N.; Kumar, S.; Sugai, H. (J. Appl. Phys., 2001)

(untitled) - Ostrikov, K. N.; Kumar, S.; Sugai, H. (Phys. Plasmas, 2001)

(untitled) - Teare, D. O. H.; Spanos, C. G.; Ridley, P.; Kinmond, E. J.; Roucoules, V.; Badyal, J. P. S.; Brewer, S. A.; Coulson, S.; Willis, C. (Chem. Mater., 2002)

(untitled) - Fu, G. D.; Kang, E. T.; Neoh, K. G. (J. Phys. Chem. B, 2003)

(untitled) - Feng, J. C.; Huang, W.; Fu, G. D.; Kang, E.-T.; Neoh, K.-G. (Plasma Processes Polym., 2005)

(untitled) - Yang, S. H.; Liu, C.-H.; Hsu, W.-T.; Chen, H. (Surf. Coat. Technol., 2009)

(untitled) - Paquet, C.; Kumacheva, E. (Mater. Today, 2008)

(untitled) - Yonamine, Y.; Yoshimatsu, K.; Lee, S.-H.; Hoshino, Y.; Okahata, Y.; Shea, K. J. (ACS Appl. Mater. Interfaces, 2013)

(untitled) - Zhang, H.; Wu, F.; Li, Y.; Yang, X.; Huang, J.; Lv, T.; Zhang, Y.; Chen, J.; Chen, H.; Gao, Y.; Liu, G.; Jia, L. (Beilstein J. Nanotechnol., 2016)

(untitled) - Kuhn, D. A.; Vanhecke, D.; Michen, B.; Blank, F.; Gehr, P.; Petri-Fink, A.; Rothen-Rutishauser, B. (Beilstein J. Nanotechnol., 2014)

(untitled) - Binns, C. (Surf. Sci. Rep., 2001)

(untitled) - Wan, J.; Ma, Z.; Han, M.; Hong, J.; Wang, G. (Solid State Commun., 2002)

(untitled) - Harrop, P. J. (Vacuum, 1969)

(untitled) - Pratt, I. H.; Lausman, T. C. (Thin Solid Films, 1972)

(untitled) - Holland, L.; Biederman, H.; Ojha, S. M. (Thin Solid Films, 1976)

(untitled) - Youngblood, J. P.; McCarthy, T. J. (Thin Solid Films, 2001)

(untitled) - Kholodkov, I.; Biederman, H.; Slavınská, D.; Choukourov, A.; Trchova, M. (Vacuum, 2003)

(untitled) - Pihosh, Y.; Biederman, H.; Slavinska, D.; Kousal, J.; Choukourov, A.; Trchova, M.; Mackova, A.; Boldyreva, A. (Vacuum, 2006)

(untitled) - Choukourov, A.; Hanuš, J.; Kousal, J.; Grinevich, A.; Pihosh, Y.; Slavínská, D.; Biederman, H. (Vacuum, 2006)

(untitled) - Drabik, M.; Kousal, J.; Pihosh, Y.; Choukourov, A.; Biederman, H.; Slavinska, D.; Mackova, A.; Boldyreva, A.; Pesicka, J. (Vacuum, 2007)

(untitled) - Kylián, O.; Hanuš, J.; Choukourov, A.; Kousal, J.; Slavínská, D.; Biederman, H. (J. Phys. D: Appl. Phys., 2009)

(untitled) - Mikikian, M.; Labidi, S.; von Wahl, E.; Lagrange, J. F.; Lecas, T.; Massereau-Guilbaud, V.; Géraud-Grenier, I.; Kovacevic, E.; Berndt, J.; Kersten, H.; Gibert, T. (Plasma Phys. Controlled Fusion, 2017)

(untitled) - Shelemin, A.; Nikitin, D.; Choukourov, A.; Kylián, O.; Kousal, J.; Khalakhan, I.; Melnichuk, I.; Slavínská, D.; Biederman, H. (J. Phys. D: Appl. Phys., 2016)

(untitled) - Polonskyi, O.; Kylián, O.; Solař, P.; Artemenko, A.; Kousal, J.; Slavínská, D.; Choukourov, A.; Biederman, H. (J. Phys. D: Appl. Phys., 2012)

(untitled) - Howling, A. A.; Sansonnens, L.; Dorier, J.-L.; Hollenstein, C. (J. Phys. D: Appl. Phys., 1993)

(untitled) - Berndt, J.; Kovačević, E.; Stefanović, I.; Boufendi, L. (J. Appl. Phys., 2009)

(untitled) - Kovacevic, E.; Berndt, J.; Strunskus, T.; Boufendi, L. (J. Appl. Phys., 2012)

(untitled) - van de Wetering, F. M. J. H.; Beckers, J.; Kroesen, G. M. W. (J. Phys. D: Appl. Phys., 2012)

(untitled) - Blažek, J.; Kousal, J.; Biederman, H.; Kylián, O.; Hanuš, J.; Slavínská, D. (J. Phys. D: Appl. Phys., 2015)

(untitled) - Mamunuru, M.; Le Picard, R.; Sakiyama, Y.; Girshick, S. L. (Plasma Chem. Plasma Process., 2017)

(untitled) - Mangolini, L.; Kortshagen, U. (Phys. Rev. E: Stat., Nonlinear, Soft Matter Phys., 2009)

(untitled) - Maurer, H. R.; Kersten, H. (J. Phys. D: Appl. Phys., 2011)

(untitled) - Du, Y.-Z.; Tomohiro, T.; Kodaka, M. (Macromolecules, 2004)

(untitled) - Haberland, H.; Karrais, M.; Mall, M.; Thurner, Y. (J. Vac. Sci. Technol., A, 1992)

(untitled) - Solař, P.; Melnichuk, I.; Artemenko, A.; Polonskyi, O.; Kylián, O.; Choukourov, A.; Slavínská, D.; Biederman, H. (Vacuum, 2015)

(untitled) - Serov, A.; Choukourov, A.; Melnichuk, I.; Shelemin, A.; Kuzminova, A.; Kylián, O.; Hanuš, J.; Kousal, J.; Drábik, M.; Slavínská, D.; Biederman, H. (Surf. Coat. Technol., 2014)

(untitled) - Pereira, J.; Massereau-Guilbaud, V.; Géraud-Grenier, I.; Plain, A. (Plasma Processes Polym., 2005)

(untitled) - Massereau-Guilbaud, V.; Pereira, J.; Géraud-Grenier, I.; Plain, A. (J. Appl. Phys., 2009)

(untitled) - Klages, C.-P.; Kotula, S. (Plasma Processes Polym., 2016)

(untitled) - d’Agostino, R.; Favia, P.; Förch, R.; Oehr, C.; Wertheimer, M. R. (Plasma Processes Polym., 2010)

(untitled) - Balasubramanian, B.; Kraemer, K. L.; Reding, N. A.; Skomski, R.; Ducharme, S.; Sellmyer, D. J. (ACS Nano, 2010)

(untitled) - Yasar-Inceoglu, O.; Zhong, L.; Mangolini, L. (J. Phys. D: Appl. Phys., 2015)

(untitled) - Choukourov, A.; Solar, P.; Polonskyi, O.; Hanus, J.; Drabik, M.; Kylian, O.; Pavlova, E.; Slavinska, D.; Biederman, H. (Plasma Processes Polym., 2010)

(untitled) - Kousal, J.; Polonskyi, O.; Kylián, O.; Choukourov, A.; Artemenko, A.; Pešička, J.; Slavínská, D.; Biederman, H. (Vacuum, 2013)

(untitled) - Solař, P.; Polonskyi, O.; Choukourov, A.; Artemenko, A.; Hanuš, J.; Biederman, H.; Slavínská, D. (Surf. Coat. Technol., 2011)

(untitled) - Solař, P.; Kylián, O.; Polonskyi, O.; Artemenko, A.; Arzhakov, D.; Drábik, M.; Slavínská, D.; Vandrovcová, M.; Bačáková, L.; Biederman, H. (Surf. Coat. Technol., 2012)

(untitled) - Robbie, K.; Friedrich, L. J.; Dew, S. K.; Smy, T.; Brett, M. J. (J. Vac. Sci. Technol., A, 1995)

(untitled) - Boduroglu, S.; Cetinkaya, M.; Dressick, W. J.; Singh, A.; Demirel, M. C. (Langmuir, 2007)

(untitled) - Cetinkaya, M.; Boduroglu, S.; Demirel, M. C. (Polymer, 2007)

(untitled) - Kylian, O.; Shelemin, A.; Solar, P.; Choukourov, A.; Hanus, J.; Vaidulych, M.; Kuzminova, A.; Biederman, H. (Thin Solid Films, 2017)